2019
DOI: 10.1371/journal.pone.0225220
|View full text |Cite
|
Sign up to set email alerts
|

Are primary school children attending full-day school still engaged in sports clubs?

Abstract: PurposeSchools and organized sports both offer great chances to promote physical activity among children. Full-day schools particularly allow for extensive participation in extra-curricular physical activities. However, due to time reasons, full-day schools may also prevent children from engagement in organized sports outside school. There is only little national and international research addressing the possible competition of full-day schools and providers of organized sports outside school and the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…It has been shown that sports club members are more physically active than non-members [ 37 ] potentially leading to higher motor performance. Furthermore, it can be suggested that more frequent PE lessons do not compete with sports club participation which is also supported by previous observations [ 5 , 38 ], although controversial results exist [ 39 ]. Consequently, training in sports clubs is suggested to form an effective complement to PE lessons [ 2 ].…”
Section: Discussionsupporting
confidence: 67%
“…It has been shown that sports club members are more physically active than non-members [ 37 ] potentially leading to higher motor performance. Furthermore, it can be suggested that more frequent PE lessons do not compete with sports club participation which is also supported by previous observations [ 5 , 38 ], although controversial results exist [ 39 ]. Consequently, training in sports clubs is suggested to form an effective complement to PE lessons [ 2 ].…”
Section: Discussionsupporting
confidence: 67%
“…This enables full-day school children to spend their time less sedentary and more active in ASPs as compared with half-day school children who potentially spend the early afternoon at home. On the other hand, referring data of this study, Spengler et al ( 35 ) showed that full-day school children are less engaged in organized sports outside school than are half-day school children. Furthermore, weekly duration of training in sports clubs is significantly higher in half-day school children compared with full-day school children.…”
Section: Discussionsupporting
confidence: 41%
“…Selected schools were full-day schools, providing either a mandatory or optional full-day school branch. The school organization form was selected in cooperation with the responsible Ministry of Education and Cultural Affairs Baden-Wuerttemberg (see Spengler et al, 2019 ). The study was approved by the Ethics Committee of the University of Konstanz, Germany (approval number: 08/2019), and was conducted in accordance with the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%